Worldwide national intervention of developmental screening programs in infant and early childhood - Seunghyo Kim (The Korean Pediatric Society, 2022)
The prevalence of developmental disabilities is increasing worldwide over time. Developmental issues in infancy or early childhood may cause learning difficulties or behavioral problem in school age, further adversely affecting adolescent quality of life, which finally lead to low socioeconomic status in family, increase in medical expenses, and other relevant issues in various ways. Early childhood has brain plasticity, which means there is high chance of recovering from developmental issues by early detection and timely intervention. Pediatricians are placed an ideal position to meet with young children till 6 years of age, of which age range is the time applicable to early intervention. Determining child's developmental status can be made by 2 pathways such as developmental surveillance and developmental screening tests. For better results, pediatricians should update their knowledge about developmental issues, risk factors, screening techniques through varying educational program or other relevant educating materials. This paper will update reports on the prevalence of developmental disabilities and review the recent results of Korean developmental screening test and discuss relevant issues. Finally, it will be addressed the pediatrician's role in early detecting developmental issues and timely intervention.